Empowering the Role of Community Leaders in Disaster Management in Flash Flood–Prone Areas of Padang City - Rahmi Muthia; Tiurmaida Simandalahi; Muthmainnah; Fitri Mailani (Warta Pengabdian Andalas, 2026)
Padang frequently experiences flash and regular floods, resulting in material losses and casualties. Batu Busuk, due to its geographical characteristics, is highly prone to flash floods, making community preparedness essential for disaster risk reduction. To strengthen mitigation efforts, a focused group discussion (FGD) was conducted on 15 September 2023 with nine community leaders. The discussion generated three themes: the impact of the January 23, 2023 flash flood, challenges in previous disaster management, and future plans for flood mitigation. The FGD highlighted the need to increase community awareness, enhance emergency response skills, and provide adequate evacuation routes and facilities. As a follow-up, disaster mitigation education was delivered to 40 households through sessions at the local mushala and door-to-door visits, aiming to improve residents’ knowledge and preparedness. The study recommends empowering community leaders to implement disaster management plans, expanding mitigation education, facilitating structural measures, developing early warning systems, and conducting evacuation and first aid training for flash flood victims.